Comparison of dominant and nondominant leg strength and hamstring: Quadriceps ratio in professional basketball players - Aslankeser, Z.; Ceylan, B.; Revan, S. (Kinesiologia Slovenica, 2022)
The literature has revealed that knee injuries are the most common injury among basketball players. The strength ratios dominant/non-dominant and posterior-anterior around the knee joint are used to evaluate strength balances. But there has been far less research published about strength evaluation in professional-level basketball. The objectives of the present study were: (i) to compare hamstring and quadriceps muscles` strength values during concentric knee extension and flexion at different angular velocities at professional level basketballers, (ii) to determine dominant and non-dominant strength values during these contractions. 13 professional male basketball athletes voluntarily participated in the study. The leg strength was evaluated with an isokinetic dynamometer at 240- 180-120-600/s angular velocities. The hamstring and quadriceps unilateral peak torque ratio (H/Q) and dominant non-dominant strength ratio were calculated. The independent t-test was computed to bilateral and unilateral strength outputs. There was no statistically significant difference between dominant and non-dominant strength values at peak torque, normalized peak torque, and H/Q at all angular velocities. Relative peak torque outputs in both legs were similar at all angular velocities. Also, the H/Q was calculated as =0.60 in all velocities. The results of this study suggest there were not any significant differences in the unilateral and bilateral evaluations of professional basketballers. These nonsignificant differences could be related to the necessity to maintain similar strength of two legs.